Consultant Dependency in Complex Automation Projects: Implications for the Work Environment - Axelsson, Matilda (Nordic Journal of Working Life Studies, 2025)
This study explores organizational work environment issues related to the dynamics of client-consultant teams in complex automation projects. Focusing on a Swedish industrial company’s long-term collaboration with a consultancy firm to implement HR process automation, the study highlights how the interplay between knowledge and power shape the collaboration, stakeholder salience, and project success. Grounded in Nordic traditions of user-participation and democracy, it draws attention to how automation initiatives affect structural working conditions, job demands, and resources. This qualitative, single-case study, featuring participatory observations and semi-structured interviews, reveals the importance of addressing work environment issues at an organizational level and underscores the challenges of ensuring knowledge transfer, balancing stakeholder interests, and maintaining agile, collaborative prac-tices. The findings contribute to current Nordic and global discourses by demonstrating how client–consultant relationships and dependency can transform an organization’s conditions and requirements for work, emphasizing the need for a strategic approach to project management.